Developing East Java Local Wisdom-based Puppet Character Drama Video for fourth Grader in Elementary Schools - Yermiandhoko, Yoyok; Sukartiningsih, Wahyu; Wicaksono, Vicky Dwi; Choirunnisa, Nadia Lutfi; Istiq’faroh, Nurul; Damayanti, Maryam Isnaini; Zafira, Ruwaida (Tauladan Fathimah Azzahra, 2023)
Globalization changes have an impact on several sectors, one of which is education. These changes have both positive and negative effects. The advancement of science and technology has had the most visible positive impact on globalization changes. When globalization erase local culture, it has a negative impact. This research develops a product in the form of a hand puppet drama video by integrating local wisdom. This study used ADDIE developmental model. Data were collected using interviews and questionnaires. The developed local wisdom-based hand puppet drama videos in this study were validated by three experts, namely material, language and media experts. Material validation obtained a percentage of 91,6% categorized as very proper, language validation obtained a percentage of 82,5% categorized as proper, and media expert with a percentage of 92,8% included in the category very proper Student response tests revealed scores 92,7%As a result, the findings of this study are expected to provide innovation in the form of local wisdom used in current learning, specifically in 21st Century.